Power, pedagogy and the personal: feminist ethics in facilitating a doctoral writing group. Issue 1 (2nd January 2019) - Danvers, Emily; Hinton-Smith, Tamsin; Webb, Rebecca
ABSTRACT: The paper explores questions of power arising from feminist facilitators running a doctoral writing group at a UK university. Butler's [2014. Re-thinking Vulnerability and Resistance. [Online]. Accessed September 12, 2017. http://www.institutofranklin.net/sites/default/files/files/Rethinking%20Vulnerability%20and%20Resistance%20Judith%20Butler.pdf ] theorisation of precarity and vulnerability inspired us to re-think normative constructions of research writing and the academic identities and subjectivities this presupposed. Our doctoral writing group was imagined as a space to think collectively and reflexively about the thesis, the multi-faceted power-dynamics at work in its production, and our relations to the text as both writer and audience. This paper antagonises some of the pedagogic consequences of inviting seemingly 'personal' matters into the space of the writing space and, subsequently, the doctoral text itself. We speak back to discourses that position doctoral writing as always and only an individual, and individualising endeavour, that eschews encounters with the personal and relational. Indeed, we recognise that configurations and spaces for research writing are always 'political'.